The mycommunityinfo.ca Approach to Online Networked Community Information Provision - Lambert, Frank (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Mycommunityinfo.ca offers online community information (CI) by rejecting the traditional CI directory model of excessive metadata. This dynamic and sustainable approach to providing online CI through single window access to local community and three levels of government information sources also offers an unprecedented glimpse into CI needs in Southwestern Ontario. Mycommunityinfo.ca offre de l’information communautaire (IC) virtuelle en rejetant le modèle traditionnel des répertoires de l’IC utilisant de nombreuses métadonnées. Cette approche dynamique et renouvelable offrant de l’IC virtuelle, grâce à une fenêtre unique pour l’accès à la communauté locale et à trois niveaux de sources d’information gouvernementales, propose également une perspective inédite sur les besoins en IC du sud-ouest de l’Ontario.